Effectiveness and feasibility of self-sampling for human papillomavirus testing for internet-based cervical cancer screening - Li, Jingran; Wu, Ruifang; Qu, Xinfeng; Huang, Xia; Li, Ling; Lin, Zhixin; Zhang, Zhijun; Deng, Jihong; Liu, Rong; Zhao, Xiaofeng; Zhang, Songling; Lin, Bei; et al. (Frontiers in Public Health, 2022)
Objectives: Worldwide, around 18.2% of cervical cancer occurred in China, mainly because of lower screening coverage and screening quality in regional disparities. To assess self-sampling for human papillomavirus (HPV) testing, combined with the internet, as a primary cervical cancer screening (CCS) method in low-resource settings, and to establish an internet-based self-sampling CCS-management model. Methods: The women who participated registered on a CCS website. We recruited 20,136 women, aged 30–59 years, from 13 provinces in China, to perform vaginal self-sampling for HPV testing as a primary CCS, based on the internet. A questionnaire was subsequently used to investigate the acceptability of self-sampling. Results: Of the 20,103 women with qualified samples, 35.80% lived in remote areas, 37.69% had never undergone CCS, 59.96% were under-screened, and the overall prevalence of a high-risk of HPV was 13.86%. Of 8,136 respondents, 95.97% of women felt that self-sampling was easy to perform, 84.61% had no discomfort when using a self-sampling brush, 62.37% women were more likely to choose self-sampling for CCS in future, and 92.53% were willing to introduce the concept to others around them. The reliability and ease of self-sampling were independent factors influencing selection of self-sampling (p < 0.05). Conclusions: The Internet-facilitated self-sampling for HPV testing and management model for cervical cancer prevention is feasible and effective. It can be used as a supplement to the conventional screening, particularly in outlying areas with few medical resources, to improve the coverage of CCS.